The evolution of extracellular matrix - Özbek, Suat; Balasubramanian, Gnana Prakash (Molecular biology of the cell, 2010)
We present a perspective on the molecular evolution of the extracellular matrix (ECM) in metazoa that draws on research publications and data from sequenced genomes and expressed sequence tag libraries. ECM components do not function in isolation, and the biological ECM system or “adhesome” also depends on posttranslational processing enzymes, cell surface receptors, and extracellular proteases. We focus principally on the adhesome of internal tissues and discuss its origins at the dawn of the metazoa and the expansion of complexity that occurred in the chordate lineage. The analyses demonstrate very high conservation of a core adhesome that apparently evolved in a major wave of innovation in conjunction with the origin of metazoa. Integrin, CD36, and certain domains predate the metazoa, and some ECM-related proteins are identified in choanoflagellates as predicted sequences. Modern deuterostomes and vertebrates have many novelties and elaborations of ECM as a result of domain shuffling, domain innovations and gene family expansions. Knowledge of the evolution of metazoan ECM is important for understanding how it is built as a system, its roles in normal tissues and disease processes, and has relevance for tissue engineering, the development of artificial organs, and the goals of synthetic biology.